2018
DOI: 10.1055/s-0037-1621702
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Data Quality Management within Clinical Trials

Abstract: Clinical trial sites are implementing ad hoc methods pragmatically to ensure data quality. Findings highlight the necessity for further research into "standard practice" focusing on developing and implementing publically available data quality monitoring procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Across trials it is observed that those with 2 arms and a 1:1 randomization to drug or placebo have smaller placebo responses (and larger drug-placebo differences) than multi-arm trials [ 98 ]. Central review of the collection of the primary outcomes measures and the entry criteria (at randomization) helps ensure that the behavioral changes are accurately rated and sufficiently severe to meet the randomization criteria [ 99 ]. Central reviewers listen to a recorded audio tape of the interview or may watch a videotaped interview.…”
Section: Reviewmentioning
confidence: 99%
“…Across trials it is observed that those with 2 arms and a 1:1 randomization to drug or placebo have smaller placebo responses (and larger drug-placebo differences) than multi-arm trials [ 98 ]. Central review of the collection of the primary outcomes measures and the entry criteria (at randomization) helps ensure that the behavioral changes are accurately rated and sufficiently severe to meet the randomization criteria [ 99 ]. Central reviewers listen to a recorded audio tape of the interview or may watch a videotaped interview.…”
Section: Reviewmentioning
confidence: 99%
“…Previous studies about clinical drug trial quality usually focused on specific aspects, such as trial design, 5 subject recruitment, 6,7 rights protection, [8][9][10][11][12][13][14] role of nurses, [15][16][17][18] control of side effects 16,19 and trial data 20,21 from a micro-perspective. Further, Moher et al, 2 Verhagen et al, 22 Maher et al 23 and Liu et al 24 undertook comprehensive studies that analysed the components, determinants and evaluation instruments with respect to quality of clinical trials: such efforts emphasize the design or implementation of trials at the micro-level.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…Unlike randomized clinical trials (RCTs), data validation for critical variables is rarely reported in observational studies. Although many data monitoring and auditing methods in RCTs have been frequently reported and compared [ 9 11 ], on-site source data verification (SDV) is still a common procedure to ensure high data quality in RCTs [ 12 ]. Since SDV is a very expensive and personnel-intensive method [ 13 ] and observational studies are often limited in its financial, time, and personnel resources, this approach is not feasible in most cases.…”
Section: Introductionmentioning
confidence: 99%